Are you talking to the future me? The moderator role of future self‐relevance on the effects of aging salience in retirement savings. Issue 7 (23rd April 2018) - Marques, Sibila; Mariano, João; Lima, Maria Luísa; Abrams, Dominic
Abstract: Increasing the salience of aging has been shown to be a promising strategy to promote young adults' interest in saving for retirement. However, the processes responsible for this effect are still largely unknown. We hypothesize that increased savings choices will only occur when participants are also engaged in self‐relevant thoughts about their own future. Participants were exposed to a fictitious website advertising financial products. Study 1 ( n  = 78; Mage  = 20.87) primed age salience and future self‐relevance orthogonally and showed that priming aging only caused increases in retirement investment decisions when self‐relevance was also high. Study 2 ( n  = 91; Mage  = 23.40) tested whether the effects of age priming were due specifically to age or to a broader focus on the future. The study confirmed that investment decision effects are specific to exposure to the aging prime and not merely priming the future. The effects were also specific to investment in retirement funds and not just depositing money in a checking account. These findings have both theoretical and practical implications for the psychology of aging and retirement planning.